Even education and experience has its limits: Closing the wage gap - Gil S. Epstein; Dalit Gafni; Erez Siniver (Bar-Ilan University, Department of Economics, 2014)
Economic outcomes are compared for university graduates in Israel belonging to four different ethnic groups. A unique dataset is used that includes all individuals who graduated with a first degree from universities and colleges in Israel between the years 1995 and 2008 and which tracks them for up to 10 years from the year they graduated. The main finding is that education and experience appear to have a strong effect on earnings in the long run and that an ethnic group can improve its position relative to specific groups while it has no effects relative to other groups.
Keywords: J15; J24; J31; 330; wage differences; immigrants; discrimination